Instructional Leadership Practices Supporting the Academic Performance of Students with Special Needs in Inclusive Public Secondary Schools in Iringa Municipality, Tanzania: A Qualitative Multiple Case Study - Andrew Emmanuel Kilipamwambu; Karoli John Mrema; Jesse John Lukindo (East African Journal of Education Studies, 2026)
Inclusive education policies in Tanzania and across Sub-Saharan Africa have expanded access for learners with special needs, yet persistent performance gaps suggest that school-level leadership, not policy alone, may influence whether inclusion translates into meaningful learning. This study examined leadership practices shaping the academic performance of students with special needs in two inclusive public secondary schools in Iringa Municipality, Tanzania, focusing on instructional leadership, inclusive school culture, and resource allocation. Anchored in Adaptive Leadership Theory, the study used a qualitative multiple case study design with 22 participants, school leaders, teachers, and students, drawing on twelve semi-structured interviews and two focus group discussions analysed thematically, with trustworthiness ensured through triangulation, member checking, and an audit trail. Findings show that instructional practices such as classroom observation, structured feedback, and differentiated instruction strengthened teachers’ inclusive capacity, though heavy workloads limited consistency. Joint planning between general and specialist teachers fostered an inclusive culture that helped most learners feel accepted, while resource-allocation decisions shaped material conditions for inclusion but were constrained by chronic underfunding. The study concludes that these three leadership dimensions function as an interdependent system rather than separate practices, and recommends coordinated investment, structured student-reporting channels, and inclusive-pedagogy training. As the study drew on participant accounts rather than examination data, academic performance is treated here as an experienced, not a measured, construct